2022
DOI: 10.3390/biomedicines10071643
|View full text |Cite
|
Sign up to set email alerts
|

circRNA: A New Biomarker and Therapeutic Target for Esophageal Cancer

Abstract: Circular RNAs (circRNAs) comprise a large class of endogenous non-coding RNA with covalently closed loops and have independent functions as linear transcripts transcribed from identical genes. CircRNAs are generated by a “back-splicing” process regulated by regulatory elements in cis and associating proteins in trans. Many studies have shown that circRNAs play important roles in multiple processes, including splicing, transcription, chromatin modification, miRNA sponges, and protein decoys. CircRNAs are highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 120 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…CircRNAs are abundant in eukaryotic cells and were originally thought to be by‐products of pre‐mRNA splicing. Nevertheless, recently, numerous studies have shown that circRNAs, as a proto‐oncogene or oncosuppressor gene, shows close relationship to the occurrence of various tumors, containing glioma, esophageal cancer, gastric cancer, lung cancer, hepatocellular carcinoma, and so on 6,26–30 . For example, circRNA _010763 induced c‐Myc expression and stimulated the proliferation and invasion of lung cancer through playing the role of a molecular sponge for miR‐715 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs are abundant in eukaryotic cells and were originally thought to be by‐products of pre‐mRNA splicing. Nevertheless, recently, numerous studies have shown that circRNAs, as a proto‐oncogene or oncosuppressor gene, shows close relationship to the occurrence of various tumors, containing glioma, esophageal cancer, gastric cancer, lung cancer, hepatocellular carcinoma, and so on 6,26–30 . For example, circRNA _010763 induced c‐Myc expression and stimulated the proliferation and invasion of lung cancer through playing the role of a molecular sponge for miR‐715 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis could determine the binding site between the occurrence of various tumors, containing glioma, esophageal cancer, gastric cancer, lung cancer, hepatocellular carcinoma, and so on. 6,[26][27][28][29][30] For example, circRNA _010763 induced c-Myc expression and stimulated the proliferation and invasion of lung cancer through playing the role of a molecular sponge for miR-715. 31 CircRNA-104 718, as a competitive endogenous RNA, stimulated the progression of liver cancer through microRNA-218-5p/TXNDC5 signaling pathway.…”
Section: Hmga1 Is the Target Of Mir-665 And Mir-370-3pmentioning
confidence: 99%
“…Current knowledge of circRNA has characterized it as noncoding RNA, and an increasing number of circRNAs have been found to be associated with pretranscription/post-transcription processes by acting as miRNA sponges, protein decoys, splicing regulators, and transcription and chromatin modifiers [ 35 , 36 , 37 ]. Because of the characteristics of circRNA, including its stable structure due to its covalently closed loops [ 38 ], redundant expression level, and easy detection, it is currently considered an optimal diagnostics biomarker for various diseases [ 39 , 40 , 41 ]. In MMD, very few diagnostic biomarkers have been identified and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that CircURI1 plays a crucial role in regulating alternative splicing of numerous genes associated with cell migration by directly binding with hnRNPM, ultimately suppressing the metastatic progression of gastric cancer. Furthermore, some endogenous circRNAs containing open reading frames have been observed to undergo translation, resulting in the production of peptides or proteins ( Shoda et al, 2022 ). However, their potential functions are still unclear.…”
Section: Circular Rnas and Lung Cancermentioning
confidence: 99%